Braving the wilderness [large type] : the quest for true belonging and the courage to stand alone - Brown, Brené (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Social scientist Brené Brown, PhD, LMSW, has sparked a global conversation about the experiences that bring meaning to our lives -- experiences of courage, vulnerability, love, belonging, shame, and empathy. Now Brown redefines what it means to truly belong in an age of increased polarization. Brown argues that we're experiencing a spiritual crisis of disconnection, and introduces four practices of true belonging that challenge everything we believe about ourselves and each other. Brown offers us the clarity and courage we need to find our way back to ourselves and to each other - and that path cuts right through the wilderness. Brown writes, "The wilderness is an untamed, unpredictable place of solitude and searching. It is a place as dangerous as it is breathtaking, a place as sought after as it is feared. But it turns out to be the place of true belonging, and it's the bravest and most sacred place you will ever stand."